Polymorphisms and expression of genes encoding Argonautes 1 and 2 in autoimmune thyroid diseases - Ena Tokiyoshi; Mikio Watanabe; Naoya Inoue; Yoh Hidaka; Yoshinori Iwatani (Taylor & Francis Group, 2018)
The microRNA (miRNA) biogenesis pathway is regulated by specific proteins and enzymes, including Dicer, Drosha, DGCR8, Exportin 5 and the Argonaute (AGO) family. In this study, we investigated the AGO family, which is the primary component of RISC (RNA-induced silencing complex) and directly binds to microRNA. We examined the association of polymorphisms in AGO family genes with AGO expression and with the development and prognosis of autoimmune thyroid diseases. We genotyped AGO1 rs636832A/G, AGO2 rs7005286C/T, AGO2 rs11166985A/G and AGO2 rs2292779C/G polymorphisms in 184 Graves' disease (GD) patients, 195 Hashimoto's disease (HD) patients and 122 healthy volunteers using the polymerase chain reaction-restriction fragment length polymorphism method. We also examined the expression of AGO1 and AGO2 mRNAs in peripheral blood mononuclear cells (PBMC) obtained from 52 GD patients, 41 HD patients, and 25 healthy volunteers using quantitative RT-PCR methods. The G allele of AGO1 rs636832 and the A allele of AGO2 rs11166985 polymorphisms were significantly more frequent in GD patients than in healthy controls. The A allele of AGO2 rs11166985 was also significantly more frequent in intractable GD patients than in controls. The C carrier (CC + CG genotypes) and C allele of AGO2 rs2292779 polymorphism were significantly more frequent in intractable GD patients than in patients with GD in remission. Expression of AGO1 mRNA in PBMC was significantly higher in AITD patient than in controls, and that of AGO2 mRNA in PBMC was significantly higher in intractable GD patients than in patients with GD in remission. Furthermore, the expression levels of both the AGO1 and AGO2 genes were significantly correlated with the proportions of Th17 cells in PBMC. In conclusion, the polymorphisms of the AGO1 and AGO2 genes, the expression levels of which correlated with the proportion of Th17 cells, were associated with the development and prognosis of GD. The AGO2 rs2292779 C carrier and C allele were associated with the intractability of GD.